Comparing retail formats in an emerging market: Influence of credit and low price guarantee on purchase intention. Issue 1 (14th May 2014) - K. Saini, Gordhan; Sahay, Arvind
Abstract : Purpose: – This study aims to examine the importance of credit and low price guarantee (LPG) on consumer purchase intention across types of retail store formats in an emerging market context. Design/methodology/approach: – A 2 (kirana/modern retail)×2 (high/low LPG)×2 (credit/no credit) experimental design was used for this study. A sample of 200 respondents was asked about their purchase intention for a newly introduced hypothetical toothpaste brand and six hypotheses were tested. Findings: – Findings show that credit and level of LPG determine consumer's purchase intention across store formats. The presence of credit and high LPG increases the purchase intention; however, relatively importance of these two varies by type of store. The absence of credit at kirana store definitely reduces the buying intention, while same is not true for modern retail store, where level of LPG is more important than the credit. Interestingly, buyer is likely to discount high LPG for a month's credit offered by a kirana store. Practical implications: – The study can help practitioners and scholars to understand consumer responses to credit and LPG in buying decisions, and subsequently in designing a better product offer at a particular store format in emerging markets. Originality/value: – Important insights are provided about the consumer behavior resulting from the presence or absence of credit and high or low levels of LPG in an emerging market context. The study also has public policy implications in a country where FDI in retail is a hotly debated topic.